Multi-tissue transcriptomic characterization of endogenous retrovirus-derived transcripts in Capra hircus - Li, Ming-Di; Li, Hu-Rong; Ye, Shao-Hui (Frontiers in Genetics, 2025)
BackgroundTransposable elements (TEs, or transposons) are repetitive genomic sequences, accounting for half of a mammal genome. Most TEs are transcriptionally silenced, whereas some TEs, especially endogenous retroviruses (ERVs, long terminal repeat retrotransposons), are physiologically expressed in certain conditions. However, the expression pattern of TEs in those less studied species, like goat (Capra hircus), remains unclear. To obtain an overview of the genomic and transcriptomic features of TEs and ERVs in goat, an important farm species, we herein analyzed transcriptomes of ten C. hircus tissues and cells under various physiological and pathological conditions.MethodDistribution of classes, families, and subfamilies of TEs in the C. hircus genome were systematically annotated. The expression patterns of TE-derived transcripts in multiple tissues were investigated at subfamily and location levels. Differential expression of ERV-derived reads was measured under various physiological and pathological conditions, such as embryo development and virus infection challenges. Co-expression between ERV-reads and their proximal genes was also explored to decipher the expression regulation of ERV-derived transcripts.ResultsThere are around 800 TE subfamilies in the goat genome, accounting for 49.1% of the goat genome sequence. TE-derived reads account for 10% of the transcriptome and their abundance are comparable in various goat tissues, while expression of ERVs are variable among tissues. We further characterized expression pattern of ERV reads in various tissues. Differential expression analysis showed that ERVs are highly active in 16-cell embryos, when the genome of the zygote begins to transcribe its own genes. We also recognized numerous activated ERV reads in response to RNA virus infection in lung, spleen, caecum, and immune cells. CapAeg_1.233:ERVK in chromosome 1 and 17 are dysregulated under endometrium development and infection conditions. They showed strong co-expression with their proximal gene OAS1 and TMPRSS2, indicating the impact of activated proximal gene expression on nearby ERVs.ConclusionWe generated ERV transcriptomes across goat tissues, and identified ERVs activated in response to different physiological and pathological conditions.